Digital Forensic Data In Technology-Based Crime Investigations: A Juridical-Empirical Review Of Obstacles And Solutions - Zain Arfin Utama Zain; Sutinnarto; Dwi Kusumawati (Institut Karya Mulia Bangsa, 2025)
Digital forensic evidence has become a critical tool in cybercrime investigations, yet its implementation in Indonesia faces normative and technical gaps. This study analyzes the urgency, evidentiary paradigms, and challenges of digital forensic data using a juridical- empirical approach and case studies (MV Run Zeng Case, 2024). Findings indicate that while Law No. 19/2016 on ITE and the Criminal Procedure Code (KUHAP) recognize digital evidence, weak chain of custody, lack of certified experts, and overlapping regulations threaten evidentiary integrity. Proposed solutions include standardizing DEFR procedures, inter-agency collaboration, and capacity-building through certified training. These findings contribute to developing adaptive digital forensics policies for Industry 5.0, balancing substantive justice and privacy protection. This research underscores that the successful implementation of digital forensic evidence depends not only on strong regulations, but also on a collective commitment to adopting global best practices. In this way, Indonesia can position itself as a pioneer in enforcing cyber law in the digital era, while maintaining a balance between public security and protecting individual rights.